Manifestation of Guillain–Barre Syndrome in a Case of Monkeypox Virus Infection: A Rare Case Report - Tariq Abdul Hamid; Nayab Mustafa; Almas Zulfiquar Parkar; Sherin Marina Varghese; Ossama Sayedahmed; Mohammed Ghanaim (Case Reports in Infectious Diseases)
Monkeypox virus (MPXV) is one of the rare zoonotic infections caused by orthopoxvirus. MPXV has recently been an evolving threat to public health with its contagious human-to-human transmission. Various presentations of MPXV infection have been reported ranging from generalised symptoms such as fever, chills, body aches, and swollen lymph nodes to dermatological presentations. Neurological manifestations that have been reported include headaches, myalgia, seizures, and even mood disturbances. Postinfectious complications such as encephalitis, vision problems, and skin infections have also been noticed. Guillain–Barre Syndrome (GBS) is an acquired acute inflammatory polyradiculoneuropathy characterized by progressive, symmetrical, proximal, and distal tingling and weakness. Although various microorganisms are known to cause GBS and have been linked to the smallpox vaccine, they are rarely linked to MPXV disease. In this report, we describe a case of a confirmed monkeypox infection in a patient presenting with Guillain-Barre Syndrome.